Brand-to-generic Levetiracetam Switch in Patients with Epilepsy: Seizure Control and its Predictors in a Real-world Setting - Tiamkao, Siriporn; Kanchanauthai, Natthawaree; Sawanyawisuth, Kittisak; Tiamkao, Somsak (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Epilepsy is a common neurological disease. Treatment with original antiepileptic drugs may result in high cost. Levetiracetam (LEV) is a broad-spectrum antiepileptic drug. Several studies showed that generic LEV is safe, effective, and saves cost. There are limited data on predictors of seizure control in persons with epilepsy treated with LEV, particularly switch therapy to generic LEV. METHODS: This study was a comparison study conducted at two tertiary care hospitals. One hospital used an original LEV, while another one switched to generic LEV. The outcomes of the study included seizure control after switching to generic LEV treatment, treatment cost, dosage of LEV, adverse events of LEV, switching therapy to original LEV, emergency room visit, and abnormal laboratory tests. These outcomes were compared between the generic and original LEV. Seizure control defined by free of seizure after switch therapy. Predictors of seizure control were analyzed by multiple logistic regression analysis. RESULTS: During the study period, there were 96 eligible patients and treated with generic LEV in 61 patients (63.54%). Regarding treatment outcomes, the generic LEV group had significantly higher proportions of seizure control (91.80% vs. 45.71%) than the original LEV group. The original LEV group had significantly higher cost than the generic LEV group (65,250 vs. 9500 Baht; p < 0.001). The final model had two factors remaining: Generic LEV and frequency of seizure before switch therapy. Generic LEV was independently associated with seizure control with adjusted OR of 6.35 (95% CI of 1.73, 23.34). CONCLUSION: Switch therapy to generic LEV is an alternative therapy with comparable efficacy, lower cost, and safe. Generic LEV and frequency of seizure attack before switch therapy to generic LEV may be related to seizure control.